2007
DOI: 10.1093/ajcn/85.3.788
|View full text |Cite
|
Sign up to set email alerts
|

Maternal intake of vitamin D during pregnancy and risk of recurrent wheeze in children at 3 y of age

Abstract: Background: Vitamin D deficiency and asthma are common at higher latitudes. Although vitamin D has important immunologic effects, its relation with asthma is unknown. Objective: We hypothesized that a higher maternal intake of vitamin D during pregnancy is associated with a lower risk of recurrent wheeze in children at 3 y of age. Design: The participants were 1194 mother-child pairs in Project Viva-a prospective prebirth cohort study in Massachusetts. We assessed the maternal intake of vitamin D during pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
486
9
13

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 629 publications
(526 citation statements)
references
References 57 publications
18
486
9
13
Order By: Relevance
“…In animal models, vitamin E, zinc and vitamin D have been shown to modify fetal lung development, and vitamin E, zinc, vitamin D and PUFA can modulate T-cell responses. In humans, birth cohort studies have reported associations between wheezing and eczema in early life and low prenatal status of selenium and iron (17) , low maternal intake of vitamin E (9,18,19) , vitamin D (20,21) , apple and fish (10,22,23) .…”
Section: Maternal Diet During Pregnancymentioning
confidence: 99%
“…In animal models, vitamin E, zinc and vitamin D have been shown to modify fetal lung development, and vitamin E, zinc, vitamin D and PUFA can modulate T-cell responses. In humans, birth cohort studies have reported associations between wheezing and eczema in early life and low prenatal status of selenium and iron (17) , low maternal intake of vitamin E (9,18,19) , vitamin D (20,21) , apple and fish (10,22,23) .…”
Section: Maternal Diet During Pregnancymentioning
confidence: 99%
“…Morales et al (18) reported that higher maternal circulating 25(OH) D concentrations in pregnancy were independently associated with a lower risk of lower respiratory tract infections in offspring in the first year of life, but not with wheezing or asthma in childhood. However, another study from the northeastern US demonstrated that a higher maternal intake of vitamin D during pregnancy may decrease the risk of recurrent wheeze in early childhood (19) .…”
Section: Introductionmentioning
confidence: 99%
“…Maternal vitamin D intake during pregnancy has previously been associated with asthma symptoms in several childhood epidemiological studies [40,41], while variants in the vitamin D receptor have been associated with asthma in genetic studies [42,43].…”
Section: Vitamin D and Asthmamentioning
confidence: 99%
“…In addition, other studies have proved that vitamin D deficiency in pregnant women may result in increased risk of respiratory tract infections in their infants [44][45][46][47][48][49]. The majority of immune cells express VDRs, mainly after they themselves have been stimulated [40,41,48]. The mechanism by which vitamin D regulates inflammation and immunity is complicated.…”
Section: Vitamin D and Asthmamentioning
confidence: 99%
See 1 more Smart Citation